Money supply impact on investment and GDP: statistical analysis - Lypnytskyi, D.V.; Lypnytska, P.D. (Економіка промисловості, 2022)
The question of how the changes in money supply influence investment and GDP have been studied intensively in recent history. However, not all aspects of this impact are sufficiently researched. In particular, the "new normality" (that has evolved recently) limits the use of well-known classical concepts and models in monetary policy, especially for emerging economies to which Ukraine belongs. Thus, the subject of this study was to assess the relationship between monetary aggregates, investment, and GDP by the world economic data analysis using mathematical statistics.
As the information base for the study, the World Bank official statistics were taken (including broad money, gross capital formation, and GDP). More than 71% of all investigated countries showed a significant correlation between M3 and gross investment. The issue of how the strength of this relationship depends on the level of socio-economic development was investigated. Classification of countries was carried out using the “nearest neighbors” method in a two-dimensional feature space, namely, per capita income and correlation tightness. The analysis showed that 79% of all countries fall into the class with a proven high correlation. Moreover, their level of wealth and development was irrelevant.
A cluster analysis of countries was fulfilled in the chosen feature space using the “mean shift” method. With the help of this method, all countries have been distributed into five clusters with different socio-economic conditions and an accuracy of 91%. Among them, there was a group of countries highly sensitive to change in monetization, up to extremely negative economic impacts.
The study helped to conclude that, regardless of economic development, GDP benefits from an increase in the money supply. Although this factor is considered necessary, it is nevertheless not sufficient for economic growth, especially in the time of the fourth industrial revolution, when the government has to play a more active and complex role in accelerating national technological development. Незважаючи на те що вплив грошової маси на інвестиції та ВВП активно досліджується, не всі аспек¬ти цього процесу вивчені достатньою мірою. Це, зокрема, пов'язано з «новою нормальністю», яка склалася останнім часом. Її особливості не дозволяють вико¬рис¬товувати класичні концепції та моделі для формування ефективної монетарної політики, тим більше у специфічних умовах емерджентної економіки, до якої належить Україна. Метою статті є визначення взаємозв'язку грошових агрегатів, інвестицій та ВВП у нових умовах шляхом аналізу часових рядів економічних даних.
Інформаційною базою дослідження є статистика Світового банку за країнами світу з показниками «широких» грошей (М3) і валових інвестицій. Статистичний аналіз дозволив встановити, що понад 71% розглянутих країн мають суттєву кореляцію між М3 та валовими інвестиціями. Визначено, наскільки сила кореляції залежить від рівня соціально-економіч¬ного розвитку. Для цього на основі методу «найближчих сусідів» здійснено класифікацію країн у двовимірному просторі: за параметрами доходу на душу населення і щільності зв'яз¬¬ку М2 та інвестицій. Аналіз свідчить, що 79% з усіх розглянутих країн опинилися в класі з доведеною високою кореляцією, причому незалежно від рівня їхнього багатства та розвитку. У цьому ж просторі ознак виконано кластерний аналіз країн із використанням методу «зрушення середнього», який дозволив із точністю 91% розподілити країни на п'ять кластерів із різними соціально-економічними умовами, а також виокремити групу країн, особливо чутливих до зниження рівня монетизації, аж до негативних наслідків для економіки.
Доведено, що незалежно від рівня розвитку економіки зростання «широкої» грошової маси є чинником, який істотно впливає на зростання ВВП. Незважаючи на те що даний чинник розглядається як необхідний, він не є достатнім для зростання економіки, особливо в період Четвертої промислової революції, коли держава має відігравати більш активну та складну роль у прискоренні національного техніко-технологічного розвитку. Несмотря на то что влияние денежной массы на инвестиции и ВВП активно исследуется, не все его аспекты достаточно изучены. В частности, сложившаяся в последние годы «новая нормальность» не позволяет использовать классические концепции и модели для формирования эффективной монетарной политики, тем более в специфических условиях эмерджентной экономики, к которой относится Украина. Целью статьи является определение взаимосвязи денежных агрегатов, инвестиций и ВВП в новых условиях посредством анализа временных рядов экономических данных.
Информационной базой исследования является статистика Мирового банка по странам мира с показателями «широких» денег (М3) и валовых инвестиций. Статистический анализ позволил установить, что более 71% рассматриваемых стран показали существенную корреляцию между М3 и валовыми инвестициями. Определено, насколько сила корреляции зависит от уровня социально-экономического развития страны. Для этого на основе метода «ближайших соседей» проведена классификация стран в двухмерном пространстве: по параметрам дохода на душу населения и тесноты связи М2 и инвестиций. Анализ показал, что 79% из всех анализируемых стран оказались в классе с доказуемой высокой корреляцией, причем независимо от уровня их богатства и развития. В том же пространстве признаков выполнен кластерный анализ стран с использованием метода «сдвига среднего». Этот метод позволил с точностью 91% разделить страны на пять кластеров с различными социально-экономическими условиями, а также выделить отдельную группу стран, особенно чувствительных к снижению уровня монетизации, вплоть до самых негативных последствий для экономики.
Доказано, что независимо от уровня развития экономики рост «широкой» денежной массы является фактором, существенно влияющим на рост ВВП. Несмотря на то что этот фактор рассматривается как необходимый, он, тем не менее, не является достаточным для роста экономики, особенно в период Четвертой промышленной революции, когда государство должно играть более активную и сложную роль в ускорении национального технико-технологического развития.